Is blood flow to the brain different in rowers? (2015)
New research suggests that there may be something special about rowing. The blood flow to the brain during rowing could in fact be different to that of other sports. For instance, there is some evidence that blood flow to the brain does increase in the afternoon. It is hypothesized that this might be coupled to increased endurance performance in the afternoon.